ТИЛ БИЛИМИНДЕ ЖУМБАҚЛАРДЫҢ ЛИНГВОФОЛЬКЛОРИСТИКАЛЫҚ БАҒДАРДА ИЗЕРТЛЕНИЎИ - Наубетуллаева, Э. (FAN va JAMIYAT, 2021)
The article discusses linguistic and folklorisic study of riddles in the Russian language, Turkic studies and the Karakalpak language, the relevance of studying the language of riddles and tasks. The study of the linguistic features of folklore is a source of information about the history of the people, the history of the language.